1997
DOI: 10.2135/cropsci1997.0011183x003700020002x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Mega‐Environments and Targeting Genotypes

Abstract: To maximize yield throughout a crop's heterogeneous growing region, despite differences in cultivar rankings from place to place due to genotype‐environment interactions, frequently it is necessary to subdivide a growing region into several relatively homogeneous mega‐environments and to breed and target adapted genotypes for each mega‐environment. The objectives of this study are to identify relevant criteria for evaluating mega‐environment analyses and to apply the Additive Main Effects and Multiplicative In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
538
2
25

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 619 publications
(586 citation statements)
references
References 0 publications
21
538
2
25
Order By: Relevance
“…Classifying environments based on the winning genotypes (raw data), i.e., those with the highest means in each environment (Gauch and Zobel, 1997), six megaenvironments were formed (RB987935 in E1, E5 and E8; RB925211 in E2; RB935641 in E4 and E6; RB937570 in E3; RB987934 in E7; RB867515 in E9). On the other hand, based on the predicted means obtained from AMMI2 (F R Cornelius), three mega-environments were formed.…”
Section: --------------------% ---------------------mentioning
confidence: 99%
See 3 more Smart Citations
“…Classifying environments based on the winning genotypes (raw data), i.e., those with the highest means in each environment (Gauch and Zobel, 1997), six megaenvironments were formed (RB987935 in E1, E5 and E8; RB925211 in E2; RB935641 in E4 and E6; RB937570 in E3; RB987934 in E7; RB867515 in E9). On the other hand, based on the predicted means obtained from AMMI2 (F R Cornelius), three mega-environments were formed.…”
Section: --------------------% ---------------------mentioning
confidence: 99%
“…The additive main effect and multiplicative interaction (AMMI) method integrates analysis of variance (ANOVA) and principal component analysis (PCA) into a unified approach that can be used to analyse multilocation trials Crossa et al, 1990;Gauch and Zobel, 1996). AMMI uses analysis of variance to study the main effects of genotypes and environments and a principal component analysis for the residual multiplicative interaction among genotypes and environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was similar to studies in which environmental effects were shown to be responsible for approximately 80% or more of the total experimental variation in wheat grain yield (Atlin and McRae 1994;Mohammadi et al 2010;Tapley et al 2013). Gauch and Zobel (1997) reported that locations accounted for approximately 80% of total variation, whereas genotype and G×E interactions each accounted for approximately 10%. In our study, relatively high values of variance components for the environmental effects (YR and YL(R)) confirmed that agro-ecological conditions in the trial locations varied, which caused most of the yield variation in the winter wheat PVTS.…”
Section: Discussionmentioning
confidence: 99%